Proposition of new secure data communication technique based on Huffman coding, chaos and LSB. (8th March 2021) - Bouguessa, Abdelkader; Said, Naima Hadj; Pacha, Adda Ali
As the number of internet users grow, finding robust and secure data communication is becoming increasingly popular today. This issue has led to the creation of hybrid security mechanisms. There are several methods in the literature that use various methods of encryption and steganography with certain advantages and disadvantages. This work provides a new hybrid security mechanism that tries to integrate the theory of chaos as cryptography mechanism, with LSB steganography technique. Huffman coding has also been used to increase the ability to integrate the proposed mechanism. Another new thing in this work is that we use a specific presentation to send plaintext data inside a picture. Our proposals are tested in MATLAB. To examine the effectiveness of the proposed technology, three types of analysis are performed: security, robustness and efficiency analysis. Modelling and results show that the proposed method is beating other methods in the literature.